2015
DOI: 10.1186/s40064-015-1056-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological profile and antimicrobial susceptibility patterns of blood culture isolates among febrile patients in Mekelle Hospital, Northern Ethiopia

Abstract: Bacterial bloodstream infections are a major public health problem, which leads to high morbidity and mortality of patients. On time diagnosis and appropriate medication will be the best way to save the lives of affected ones. The aim of the present study was to determine the bacterial profile of bloodstream infections and their antibiotic susceptibility pattern in Mekelle Hospital. Cross sectional study method was carried out in 514 (269 females and 245 males) febrile patients in Mekelle hospital from March t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
58
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 23 publications
35
58
7
Order By: Relevance
“…CoNS and Enterococcus species isolates showed higher level of resistance to beta-lactam antibiotics than Staphylococcus aureus, which is similar to other studies. 40 Antimicrobial resistance profile of Gram-negative bacteria showed a higher rate of resistance as compared with Gram-positive bacteria as has also been shown in these studies. 39,40 Most of the Gram-negative bacteria were multidrug resistant with a very high resistance to beta-lactam antibiotics.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…CoNS and Enterococcus species isolates showed higher level of resistance to beta-lactam antibiotics than Staphylococcus aureus, which is similar to other studies. 40 Antimicrobial resistance profile of Gram-negative bacteria showed a higher rate of resistance as compared with Gram-positive bacteria as has also been shown in these studies. 39,40 Most of the Gram-negative bacteria were multidrug resistant with a very high resistance to beta-lactam antibiotics.…”
Section: Discussionsupporting
confidence: 73%
“…40 Antimicrobial resistance profile of Gram-negative bacteria showed a higher rate of resistance as compared with Gram-positive bacteria as has also been shown in these studies. 39,40 Most of the Gram-negative bacteria were multidrug resistant with a very high resistance to beta-lactam antibiotics. Meropenem resistance was seen in 10-30% isolates.…”
Section: Discussionsupporting
confidence: 73%
“…Two (2/19, 10.6%) [ 16 , 17 ] of the studies which reported on Citrobacter spp. were from HAI; five (5/19, 26.3%) from community acquired infections of which three (3/5) came from pregnant women at antenatal care follow up [ 18 20 ] and two (2/5) had unknown risk factors [ 21 , 22 ]. S .…”
Section: Resultsmentioning
confidence: 99%
“…When compared with the rural areas of other countries such as Korea, Philippines, India, Venezuela, Mexico, Peru, Kenya, Ghana Zimbabwe and Etiopia [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] , the maximum levels of resistance were found in amoxicillin and oxytetracycline. The highest maximum levels of resistance in urban areas were found in amoxicillin, oxytetracycline, and trimethoprim.…”
Section: Discussionmentioning
confidence: 99%